Anti-Inflammatory and Restorative Effects of Olives in Topical Application - Mahdiyeh Taheri; Leila Amiri-Farahani (Hindawi Limited, 2021)
Background and Objective. Olive oil is used as a traditional treatment for wounds, sores, and infections, and the effectiveness of topical use and absence of side effects have been reported in various clinical trials. The present study is an overview of the anti-inflammatory properties of olive oil in its topical application for various skin diseases and wounds. Methods. A literature search was conducted (1990-2021) in Medline, Embase, CINAHL, Google Scholar, Science Direct, SID, IranDoc, and Magiran databases. From the 102 reviewed articles, 17 articles were selected to be included in the current article. Results. Various forms of olive have long been used to accelerate the healing of various wounds and skin damage such as diabetic foot ulcers, atopic dermatitis, diaper dermatitis, episiotomy wound, and nipple ulcer but there are still no credible documents or articles that provide reliable evidence of topical use. Conclusion. According to the information obtained from the articles reviewed, olive oil appears to be an effective, safe, and available treatment. This study suggests that olive oil is an alternative remedy to minimize the frequent use of chemical-based treatments. More research may be beneficial to reach certainty in terms of curative properties of olive oil in similar or different injuries in different populations.